(untitled) (The Review of Diabetic Studies, 2023)
Diabetes is a chronic metabolic disorder that is characterized by hyperglycemia due to lack of or resistance to insulin. Patients with diabetes are frequently afflicted with ischemic vascular disease and impaired wound healing. Type 2 diabetes (T2D) is known to accelerate atherosclerotic processes, endothelial cell dysfunction, glycosylation of extracellular matrix proteins, and vascular denervation. Herbal medicines and naturally occurring substances may positively affect diabetes management, and could thus be utilized as costeffective means of supporting treatment in developing countries. Natural treatments have been used in these countries for a long time to treat diabetes. The present review analyses the features of aberrant angiogenesis, abnormalities in growth factors, oxidative stress, and metabolic derangements relevant to diabetes, and how herbal substances and their active chemical constituents may counteract these events. Evidence for possible biochemical effectiveness and limitations of herbal medicines are given, as well as details regarding the role of cytokines and nitric oxide.